2021
DOI: 10.1021/acscentsci.1c00843
|View full text |Cite
|
Sign up to set email alerts
|

DNAzyme-Based Lithium-Selective Imaging Reveals Higher Lithium Accumulation in Bipolar Disorder Patient-Derived Neurons

Abstract: Lithium has been a drug for bipolar disorders (BD) for over 70 years; however, its usage has been limited by its narrow therapeutic window (between 0.6 and 1.2 mM). Understanding the cellular distribution of lithium ions (Li + ) in patient cells will offer deep insight into this limitation, but selective imaging of Li + in living cells under biomedically relevant concentration ranges has not been achieved. Herein, we report in vitro selection and development of a Li + -specific DNAzyme fluorescent sensor with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…While glucose is non‐charged, salt can bridge the highly negatively charged aptamer to promote aptamer binding. A DNA aptamer motif for specific binding of Na + is already known, [36] and DNAzymes specific for Na + and Li + were also reported [37,38] . Thus, it is understandable that this aptamer can achieve specific Na + ‐mediated glucose binding.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…While glucose is non‐charged, salt can bridge the highly negatively charged aptamer to promote aptamer binding. A DNA aptamer motif for specific binding of Na + is already known, [36] and DNAzymes specific for Na + and Li + were also reported [37,38] . Thus, it is understandable that this aptamer can achieve specific Na + ‐mediated glucose binding.…”
Section: Resultsmentioning
confidence: 92%
“…A DNA aptamer motif for specific binding of Na + is already known, [36] and DNAzymes specific for Na + and Li + were also reported. [37,38] Thus, it is understandable that this aptamer can achieve specific Na + -mediated glucose binding.…”
Section: Two Sodium Ions Are Required For Glucose Bindingmentioning
confidence: 99%
“…They then demonstrated the fluorescence detection of TPP in whole blood via the mix-and-read operation. In addition, McGhee et al reported the selection and development of a Li + -specific DNAzyme sensor with >100-fold selectivity compared with other biorelevant metal ions [ 56 ]. As shown in Figure 4 b, the fluorescent sensor is designed for imaging of Li + in HeLa cells, human neuronal progenitor cells, and neurons.…”
Section: Native Nucleic Acidsmentioning
confidence: 99%
“…Lu group reported the first example of NaA43 DNAzyme that was highly specific for the monovalent metal ions, Na + [17] . Very recently, by using the same approach of in vitro selection, they discovered another DNAzyme named 20–4 that was selective to Li + [18] . The Liu group also made efforts to select DNAzymes that were specific to monovalent and trivalent metal ions.…”
Section: Expanding Of Dnazyme Librarymentioning
confidence: 99%
“…Despite the success in divalent metal ion analysis, the sensitive and selective for monovalent ion detection is still a challenge for DNAzyme‐based sensors. Recently, the Lu group reported an RNA‐cleaving DNAzyme with high selectivity toward Li + [18] . This Li + ‐specific DNAzyme could achieve over 100‐fold selectivity compared to other biorelevant metal ions, including the two main monovalent metal ions K + and Na + in biological samples.…”
Section: Dnazyme‐based Sensing Applicationsmentioning
confidence: 99%